Technical analysis : effectiveness of technical analysis. - Lau, Kee Wee. (2008)
In the paper titled “How rewarding is technical analysis? Evidence from Singapore stock market” [Wong et al., 2003], the authors concluded that Technical Analysis, specifically Moving Average and Relative Strength Index generated profitable trades on the Singapore Exchange over a time period of 21 years. Hence, we wish to verify their results over a different time frame. While our report is not an exact comparison due to the many changes in the Straits Times Index (STI), we aim to replicate their study and see if their methods can generate profits in a different time period. Furthermore, we wish to affirm the importance of time as a factor with another market. Thus, we have selected the Hang Seng Index (HSI), as it is a similar Asian value-weighted index which has close geographical proximity with the STI. Therefore, our applied research project aims to ascertain the feasibility of the same Technical Analysis methods as those applied in [Wong et al., 2003]. Furthermore, we wish to investigate the effect of time as a factor in Technical Analysis.